JOUBERT, GJ Inventory of documents - JOUBERT, GJ (ARCA, 2018)
Genl. G.J. Joubert played a leading role in various issues of public interest. The collection contains various documents pertaining to the National Party; Voortrekker monument; Helpmekaar OVS; Bond van Oudstryders; Genl De Wet statue; Vereeniging Memorial.
COVERAGE1934-1962; 0.10 metre
Keywords: JOUBERT, GJ